CONSTRUCTION SAFETY INSPECTION PLATFORM OF HIGH-SPEED RAILWAY SUPER LARGE SWIVEL BRIDGE BASED ON NUMERICAL SIMULATION - Yongjun Zhanga; Qiangqiang Ma; Tianhui Ma; Shengrong Xie; Jun Peng (Engineering Heritage Journal)
In recent years, when building bridges across existing railways, in order to reduce the interference to the railway operation line during the construction process, parallel railways are often used to cast bridges and then rotate them. In this paper, combined with the engineering example of Zhaochuan Super Swivel Bridge on Beijing-Zhanghai High-speed Railway, the key and difficult points of the swivel bridge during construction are monitored, and compared with the computer simulation data, the static friction coefficient, dynamic friction coefficient and friction couple distance of the swivel system are obtained. Model each component of the bridge body, establish a safety monitoring and early warning method, system, storage medium, and early warning platform, and visually display the safety degree of components at different stages and locations by color discrimination.